Application of Most-Favoured-Nation Clauses by Investor-State Arbitral Tribunals Implications for the Developing Countries - Sharmin, Tanjina (International Law and the Global South, Perspectives from the Rest of the World, 2020)
XV, 302 p. 1 illus.